Could combat stress affect journalists' news reporting? A psychophysiological response (2020)
Covering war conflicts may compromise the psychological and physical health of journalists because chronic exposure to these environments has been related to depression, memory dissociative processes, and post-traumatic stress disorder; however, acute effects have not been studied yet. Thus, a combat simulation was carried out replicating actual warfare scenarios, including personnel and equipment. Psychophysiological response, memory, and information-processing were analysed of 40 professional soldiers (21 males and 19 females) and 19 journalists (12 males and 7 females) with international experience in current conflict areas such as Afghanistan, Iraq, Bosnia and Herzegovina, and Kosovo, in relation to their experience of a combat intervention. A significant increase (p < 0.05) in metabolic, muscular, cardiovascular, and cortical and psychological anxiety response, as well as a decrease in memory accuracy directly after and 24 h and 72 h post-combat were found; these modifications were modulated by the nature of the stimulus. Journalists presented higher cognitive and memory impairment than soldiers, resulting in a press reporting of real events accuracy of only 27%.